FORMULASI SABUN LOSIO PENCUCI TANGAN (HAND WASH) GEL LIDAH BUAYA (Aloevera L.) DENGAN VARIASI EMULGATOR - Audia Triani Olii (As-Syifaa Jurnal Farmasi, 2014)
The aim of the research was to determine the optimum stable physically of the hand wash.Three formula were made in vary emulsifying agents that are Span 60-Tween 60, TEA-Stearic acid and Sodium lauryl sulfate respectively. The assays carried out by accelerated condition on 5oC and 35oC for 10 cycles by which the parameter were emulsion type, creaming volume, viscosity and type of flow and dispersed globule measuring.Result showed that according to emulsion type all formula exhibited o/w indicated by blue color that even before and after conditioned. There were nothing of creaming volume in all formula.Statistic analyse in viscosity and flowing type showed that formula A insignificant before and after conditioned, and has small dispersed globule. Rheogram showed close curve so that conclusion that might be taken that formula A was the optimum one.